The Role of The Deli Serdang Police Criminal Investigation Unit (Satreskrim) In Identifying Victims of Criminal Acts - Edi Winata; Abdul Razak Nasution (International Journal of Society and Law, 2024)
The rapid development in various aspects of social, political, economic, security, and cultural life has also brought negative impacts, such as an increase in the quality and quantity of criminal acts that harm society. In formal criminal law, the primary goal is to uncover material truth. One method used to achieve this is Scientific Crime Investigation (SCI), which applies science and technology in forensic functions. The Criminal Investigation Unit (Satreskrim) plays a crucial role, particularly in the stages of investigation and victim identification in criminal cases. This study examines the role of the Satreskrim Deli Serdang Police in solving crimes through victim identification. Article 14 of Law Number 2 of 2002 on the Indonesian National Police outlines the duties of the police, including identification and forensic laboratory functions as part of investigation processes. Scientific evidence, even when minimal, often becomes a pivotal component in solving cases, especially during crime scene investigations. Focusing on accuracy and precision, the victim identification process by Satreskrim serves as the backbone of criminal investigations. This study highlights the critical role of forensic expertise and evidence-based approaches in supporting law enforcement and revealing the truth in criminal acts.